Ada S. McKinley: A Hidden History of African American Settlement House in Chicago. (19th May 2023) - Lee, KangJae Jerry; Dieser, Rodney B.
Abstract: Previous research on the history of the settlement house movement and the park and recreation profession has been dominated by celebrations of White social reformers such as Jane Addams. The stories of African American social reformers and their settlement houses have received little to no attention not only from leisure and recreation scholars, but also from the broader academic community. Using historiography and genealogy, we challenge the existing narrative and highlight the biography, activities, and legacy of Ada S. McKinley, an African American social reformer who founded the South Side Settlement House in Chicago during the first half of the twentieth century. A comparative analysis of McKinley and Addams was also conducted to promote a more nuanced understanding of their historical significance. We conclude with a summary of McKinley's contribution to the field of park and recreation and calls for more research on her and other forgotten pioneers of color.